Party funding in Italy: organizational models, empirical evidence and party self-delegitimation. Issue 4 (1st October 2020) - Piccio, Daniela R.
ABSTRACT: The article reviews the 'classic' organizational models of political parties in the light of the evolution of party financing in Italy, emphasizing agreements and disagreements. Based on the parties' official balance sheets, it presents empirical evidence on the different sources of party income over-time as well as the parties' own narrative concerning public funding from 1974, when direct public funding of political parties was introduced, until 2014, when it was repealed. It concludes that the repeal of public funding may have an important impact on party organizations, further stimulating the ongoing processes of personalization and disaggregation of political parties as cohesive units.